Salesian Charism and higher education - Farfán, Marcelo (2019)
The Salesian Institutions of Higher Education (IUS) need to generate a university culture that is the result not only of the experience, but especially of the analysis about how to do higher education. The main point of this challenge is to deepen on the relationship between the Salesian charisma and the university wold. The IUS want to be an educational project inspired by the values of the gospel and by the Salesian pedagogy originated from the Preventive System lived by Don Bosco. IUS pretend to be characterized by being academic communities that educate, unified around an institutional project defined to the service of young people. We recognize that we still do not have a Salesian tradition in the university world, but because of that, the responsibility of these first generation of Salesians and laymen committed to higher education is very important. Therefore, this publication aims to contribute to the reflection and deepening of the identity and mission of the Salesian presence in higher education, from experiences in different parts of the world and from the process developed in tHe IUS during these last two decades.